Role of Sardar Vallabhbhai Patel in Partition of India: The Role and Vision of Sardar Vallabhbhai Patel in the Partition and Unification of India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
We are extremely well acquainted with the name of Sardar Vallabhbhai Patel. He assumed a prominent role in the nation building. He was the principal appointee Prime Minister of the nation and the main Minister of Home Affairs of free India. At the season of independence India was going through a common crisis which was an aftereffect of the partition of the nation. India paid the cost of partition by losing the lives of a huge number of innocent individuals of the nation. Under such conditions Sardar Patel was given the errand of unifying the nation. Nationbuilding is conceivable just when there is harmony and for the quiet presence each part should be efficient. The solidarity and integrity are the most basic attributes of a nation. During the period of Britishers, India was isolated into various Princely States. The assignment of unification of these princely states was given to Sardar Vallabhbhai Patel. He was effectively ready to integrate these states into India. He was likewise the individual from the Constituent Assembly and thusly was one of the central planners of the present Constitution of India. This paper endeavors to accentuation on the role of Sardar Patel as the opportunity contender, in the unification of the nation, as the constitution creator, as the Deputy Prime Minister and Minister of Home Affairs, as the preeminent Commander-in-Chief of the military, and his vision in solving the present crisis in Jammu and Kashmir.